APLICAÇÃO DE MÁQUINAS DE VETORES DE SUPORTE NA INVESTIGAÇÃO DA ATIVIDADE GÊNICA DO CÂNCER DE COLO DE INTESTINO - Vieira, Sylvio Andre Garcia (2011)
Data mining is the process of discovering patterns correlated with the various existing data in a database.GEO is a public biological database, maintained by NCBI, where they sought information relating to thirty-two patients of colorectal adenoma,with readings from the probes concerning the expression of genes,extracted RNA.The data deposited in biological banks alone do not produce useful information, and therefore, were selected respecting various factors such as the reliability of the information collected, the amount of information present in the greatest number of probes, and finally filtered by reading higher expression. After the database and be treated with the selected genes was then applied to the R tool with the SVM in order to identify this small set of genes, the possibility of their association with the presence of adenoma of the colon of the intestine. From the results obtained by classifying the data it was noticed that the characteristics of the genes are distinct and that the activity varies greatly from gene to gene. However, this occurs in a standardized manner, allowing the algorithm could identify these patterns and suggest their involvement in the adenoma